Kinetics and Products of the Reactions of Ethyl and n‐Propyl Nitrates with OH Radicals. Issue 12 (13th October 2016) - Morin, Julien; Bedjanian, Yuri; Romanias, Manolis N.
ABSTRACT: The kinetics of the reactions of ethyl (1) and n ‐propyl (2) nitrates with OH radicals has been studied using a low‐pressure flow tube reactor combined with a quadrupole mass spectrometer. The rate constants of the title reactions were determined under pseudo–first‐order conditions from kinetics of OH consumption in high excess of nitrates. The overall rate constants, k 1 = 1.14 × 10 −13 ( T /298) 2.45 exp(193/ T ) and k 2 = 3.00 × 10 −13 ( T /298) 2.50 exp(205/ T ) cm 3 molecule −1 s −1 (with conservative 15% uncertainty), were determined at a total pressure of 1 Torr of helium over the temperature range (248–500) and (263–500) K, respectively. The yields of the carbonyl compounds, acetaldehyde and propanal, resulting from the abstraction by OH of an α‐hydrogen atom in ethyl and n ‐propyl nitrates, followed by α‐substituted alkyl radical decomposition, were determined at T = 300 K to be 0.77 ± 0.12 and 0.22 ± 0.04, respectively.